Pathology reporting of pancreatic cancer following neoadjuvant therapy: Challenges and uncertainties. Issue 1 (January 2015) - Verbeke, C.; Löhr, M.; Severin Karlsson, J.; Del Chiaro, M.
Highlights Key outcome measures for neoadjuvant treatment (NAT) of pancreatic cancer (PC) are pathology-based. Pathology examination of PC following NAT is difficult and lacks consensus. Variation in sampling and regression grading affects the assessment of tumour response. Margin assessment following NAT lacks an evidence-based definition. Lack of uniformity in pathology assessment hampers the study of the efficacy of NAT of PC.